2003
DOI: 10.1016/j.ehj.2003.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium enhanced cardiovascular magnetic resonance in Anderson-Fabry disease Evidence for a disease specific abnormality of the myocardial interstitium

Abstract: These observations suggests that myocardial fibrosis occurs in AFD and may contribute to the hypertrophy and the natural history of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
262
1
14

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(291 citation statements)
references
References 21 publications
14
262
1
14
Order By: Relevance
“…Like described for other cardiomyopathies, CMR is the imaging technique of choice in suspected cardiac AFD involvement. LGE within the basal infero-lateral wall without affecting the endocardium is characteristic for a cardiac manifestation in AFD [68]. In genetically confirmed AFD, Moon et al demonstrated that LGE of the infero-lateral wall was present in 50 % of the patients [68].…”
Section: Anderson Fabry Disease (Afd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Like described for other cardiomyopathies, CMR is the imaging technique of choice in suspected cardiac AFD involvement. LGE within the basal infero-lateral wall without affecting the endocardium is characteristic for a cardiac manifestation in AFD [68]. In genetically confirmed AFD, Moon et al demonstrated that LGE of the infero-lateral wall was present in 50 % of the patients [68].…”
Section: Anderson Fabry Disease (Afd)mentioning
confidence: 99%
“…LGE within the basal infero-lateral wall without affecting the endocardium is characteristic for a cardiac manifestation in AFD [68]. In genetically confirmed AFD, Moon et al demonstrated that LGE of the infero-lateral wall was present in 50 % of the patients [68]. It also seems that the presence of LGE may have a prognostic value.…”
Section: Anderson Fabry Disease (Afd)mentioning
confidence: 99%
“…In general, effects on the heart are well described as a concentric hypertrophic cardiomyopathy with reduced regional myocardial function (Breunig et al 2003;Weidemann et al 2010;Linhart et al 2000). Another key feature is myocardial replacement fibrosis, detected with cardiac magnetic resonance imaging (cMRI) (Moon et al 2003(Moon et al , 2006. In early reports, a short P-R interval was described as one of the typical alterations on electrocardiography (ECG) (Roudebush et al 1973), but a large crosssectional study failed to confirm this finding (Niemann et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial involvement in Anderson-Fabry disease leads to myocardial fibrosis, which can be visualized by late enhancement CMR imaging (129,130). The amount of fibrotic tissue as defined by late enhancement imaging correlates well with the extent of LV hypertrophy, and it is more frequently observed in the inferior lateral wall.…”
Section: Other Nonischemic Cardiomyopathiesmentioning
confidence: 99%